2005
DOI: 10.1182/blood-2004-10-3999
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of mantle-cell lymphoma by protein microarray

Abstract: Mantle-cell lymphoma (MCL) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 32 publications
5
80
0
Order By: Relevance
“…In rats, PPP5C mRNA levels markedly increased in malignant ascites hepatomas (46). Furthermore, a protein microarray analysis of mantle-cell lymphoma also revealed elevated PPP5C expression (47). With regards to PC, increased PPP5C expression was observed in PANC-1 cells treated with GEM in the present study.…”
Section: Discussionsupporting
confidence: 61%
“…In rats, PPP5C mRNA levels markedly increased in malignant ascites hepatomas (46). Furthermore, a protein microarray analysis of mantle-cell lymphoma also revealed elevated PPP5C expression (47). With regards to PC, increased PPP5C expression was observed in PANC-1 cells treated with GEM in the present study.…”
Section: Discussionsupporting
confidence: 61%
“…48 In addition, our data confirm recent gene and protein expression studies of MCL that showed overexpression of AKT pathway components. 49,50 With the exception of activated p70S6K, all of the other mTOR pathway molecules were detected primarily in the cytoplasm of MCL cells. Notably, localization of mTOR and its activated form has been reported predominantly in the cytoplasm or the nucleus, depending on the cell type and conditions, and it seems to be shuttled between the two compartments with yet unknown functional consequences.…”
Section: Discussionmentioning
confidence: 99%
“…As many as half of all human and murine lymphomas overexpress Mdm2 protein, including lymphomas that have inactivated the tumor suppressor p53 or p14/p19 ARF (Watanabe et al, 1996;Eischen et al, 1999;Alt et al, 2003;Wilda et al, 2004;Ghobrial et al, 2005). Mdm2 is an essential intermediary in the ARFp53 tumor suppressor pathway.…”
Section: Introductionmentioning
confidence: 99%